GLOBAL DISRUPTION, LOCAL ADAPTATION: REALITY TELEVISION AND GLOBO IN THE STREAMING ERA. - Rocha Vilela, Fernanda (AoIR Selected Papers of Internet Research, 2026)
The transformations brought by digital platforms and streaming services have profoundly altered the dynamics of media production and consumption in Brazil, reshaping the long-established structures of television broadcasting. Historically, TV Globo has been the dominant force in Brazil’s media landscape, pioneering national cultural production, setting audience standards, and establishing a robust international distribution network. However, the global expansion of streaming services has reconfigured traditional audiovisual models, challenging Globo’s dominance and requiring strategic shifts in content production, distribution, and monetization. This study explores Globo’s adaptation strategies by focusing on reality television—a genre that has emerged as a central pillar of the network’s response to digital platformization. It provides an important lens through which to analyse the broader restructuring of traditional broadcasters as they navigate disruptions in audiovisual models and the challenges of sustaining audience engagement in an era of fragmented media consumption.